E-government and corruption perception index: a cross-country study - Christan RA Setyobudi; Dyah Setyaningrum (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2019)
The purpose of this study is to analyse the impact of e-government on corruption perception index using a cross-country study. Furthermore, this study aims to examine the most effective e-government components in combating corruption and compare the effects of e-government in developed and developing countries. E-Government is measured using the E-Government Development Index (EGDI), consisting of online services index, human capital index, and telecommunications infrastructure index. The sample for this study consists of 521 observations from 122 countries from 2009 to2013. Our results show that there is a negative effect of e-government implementation towards corruption perception index. Furthermore, based on the elaboration of the e-government component, it was found that the variable infrastructure has a negative effect and the variable human resource dimension a positive effect on corruption perception index. This means that the development of e-government infrastructure can have a significant role in reducing perceptions of corruption in a country, while the dimensions of human resources have a dangerous side that can actually increase perceptions of corruption. There are differences in the effect of e-government on developed and developing countries. In developed countries, the implementation of e-government is in the phase of transaction and transformation which make his impact effective regarding corruption eradication. In developing countries, e-government has only reached the information and interaction phase so that it has not been effective enough to combat corruption.